2020
DOI: 10.1080/21691401.2020.1817055
|View full text |Cite
|
Sign up to set email alerts
|

Study of tissue engineered vascularised oral mucosa-like structures based on ACVM-0.25% HLC-I scaffold in vitro and in vivo

Abstract: Purpose: To explore the feasibility of constructing tissue-engineered vascularised oral mucosa-like structures with rabbit ACVM-0.25% HLC-I scaffold and human gingival fibroblasts (HGFs), human gingival epithelial cells (HGECs) and vascular endothelial-like cells (VEC-like cells). Method: Haematoxylin and Eosin (H&E) staining, immunohistochemical, immunofluorescence, 5ethynyl-2 0-deoxyuridine (EdU) staining and scanning electron microscope (SEM) were performed to detect the growth status of cells on the scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The HLC-BMP sponge prepared by Zhuoyue C ( Chen et al, 2019 ) et al can release growth factors, and it has been confirmed that it has an osteogenic induction effect in a rat calvarial defect repair model. The results of our previous study suggested that the combination of CGF and 0.75% HLC-I did not affect its good biocompatibility ( Zhou et al, 2020 ). Consistent with the above findings, our study prepared different concentrations of CGF-HLC-I (0.1, 0.25, 0.5, 0.75, 1.00%) composite biomaterials by complex cross-linking CGF with different concentrations of HLC-I.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The HLC-BMP sponge prepared by Zhuoyue C ( Chen et al, 2019 ) et al can release growth factors, and it has been confirmed that it has an osteogenic induction effect in a rat calvarial defect repair model. The results of our previous study suggested that the combination of CGF and 0.75% HLC-I did not affect its good biocompatibility ( Zhou et al, 2020 ). Consistent with the above findings, our study prepared different concentrations of CGF-HLC-I (0.1, 0.25, 0.5, 0.75, 1.00%) composite biomaterials by complex cross-linking CGF with different concentrations of HLC-I.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it needs to be compounded with other biomaterials to improve biomechanical properties. Type I collagen is the main organic component that constitutes the extracellular matrix of bones ( Du et al, 2000 ; Hong et al, 2011 ; Hempel et al, 2012 ; Zhou et al, 2020 ). Due to its excellent biocompatibility, human-like collagen has been used to composite with biomaterials to construct different biomaterial scaffolds, such as bones and blood vessels ( Hu et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding soft tissue, Qian et al revealed that combining leptin, silk fibrin, and polydopamine improves oral mucosa healing and triggers blood vessel regeneration in New Zealand rabbits ( 195 ). In addition, regeneration of oral mucosa has been previously simulated in nude mice with skin defects implanted with a human gingival endothelial cells (HGECs)-human gingival fibroblasts (HGFs)-vascular endothelial cells (VECs)-acellular vascular matrix (ACVM)-0.25% human-like collagen I (HLC-I) complex ( 204 ). In such study, investigators found that the scaffold complex had a regenerative effect based on the presence of epithelioid-like, lamina propria-like, and vascular-like structures observed on histopathological analysis.…”
Section: Translation To Clinical Practicementioning
confidence: 99%
“…Several animal studies were presented with beneficial outcomes of investigated technologies. However, some products are not intended for veterinary patients ( 179 , 195 , 196 , 199 201 , 204 , 205 ). Given the high success rates of OMF tissue engineering reported in experimental animal models and selected clinical cases, tissue engineering for OMF defect repair appears to be a viable alternative in veterinary medicine.…”
Section: Translation To Clinical Practicementioning
confidence: 99%
“…In addition, decellularized vascular matrix can be used for oral mucosa repair [ 95 ], bone tissue engineering [ 96 , 97 ], nerve repair [ 98 ], bile duct reconstruction [ 99 ], etc.…”
Section: Applications In Lymphatic Vessel Reconstructionmentioning
confidence: 99%